Change of Meaning in Space and Form of Contemporary Karo Architecture - Mohammed Nawawiy Loebis; Imam Faisal Pane; Wahyu Abdillah; Aurora S. Lubis (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Karo Plateau is one of the most valuable assets for North Sumatra Province, Indonesian. In addition to fertile soil and producing good quality vegetables and fruit, this plain also has architectural heritage to be proud of. Several villages up to now can be seen and visited which stores various Karo architectural works including some traditional buildings and houses. Change with the times, the movement of people also occurs for various reasons. The development of the city in this province makes the villagers look for livelihood in the city. However, the inheritance of ancestors was still held firmly to the present with a different format. The Karo family currently lives in shophouse and is no longer in a traditional house and they have a business there. The perception of space in traditional houses really carried over in their daily lives. Using qualitative methods, this article explains the interpretation of the different perceptions of Karo people regarding the space and form of their place of residence. However, the essence or meaning that exists in the traditional Karo architecture is still approved until now in a different form and format.